Feeds and Forages in the Livestock CGIAR Research Program - Peters, Michael; Jones, Christopher S.; Duncan, Alan J.; Castiblanco, Valheria; Ohmstedt, U.; Rüdiger, U.; Rischkowsky, Barbara A.; Burkart, Stefan (2018)
Animal Source Foods such as milk, meat and eggs are essential for human nutrition. Demand is increasing and this offers multiple opportunities for livestock producers. However, sustainable productivity and efficiency gains are needed, addressing both seasonal and inter-annual variation. Feed is a key limiting factor and often the most expensive input into livestock production. The Feeds and Forages work, organized through a flagship program, aims to respond to these bottlenecks by a) identifying and refining priorities through on-farm, large scale and global assessments; b) developing novel feed and forage options; c) better utilizes these feed options and d) identifying and testing approaches to scale these technologies through e.g. innovative business models, extension approaches and capacity building. The work in this paper would focus on novel forages, with emphasis on Eastern and Southern Africa. The aim is to identify specific needs and niches for forages and respond to this demand by developing novel forages either through selection or breeding. Advances include the availability of novel forage options either through selection e.g. of Napier grass (Cenchrus purpureus) or breeding of Brachiaria hybrids (Urochloa ruziziensis x U. brizantha x U. decumbens). The approach for scaling of these novel options through linkages with the public and private sector is being described.